The mental health of nurses who are women and mothers during the COVID-19 pandemic - Maria de Lourdes Custódio Duarte; Daniela Giotti da Silva; Larissa Gomes de Mattos; Isadora Prates Bombardi; Thayná de Almeida; Yanka Eslabão Garcia; Bruna Gottlieb Verginio (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To reflect on the mental health of nurses who are women and mothers in the context of the COVID-19 pandemic. Method: Theoretical-reflective study based on scientific literature, supported by national and international scientific literature, in addition to a critical analysis by the authors. Results: Reflections on the subject go beyond the impact of motherhood on these women's lives, as it portrays a gender issue and the role of women within society. The stress of working on the frontlines of a pandemic, added to the demands of children and housework, can trigger exhaustion and mental health repercussions. Conclusion: Workers must seek individual measures and health managers must enable collective strategies in the work environment of the institutions, proposing public policies that make both employers, workers and their families co-responsible.